HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN KESEHATAN JIWA PADA REMAJA DI SMP NEGERI 6 KOTA JAMBI: THE RELATIONSHIP BETWEEN SOCIAL MEDIA USE AND MENTAL HEALTH IN ADOLESCENTS AT SMP NEGERI 6 KOTA JAMBI - Hamidah; Ekawaty , Fadliyana; Mekeama, Luri; Amalya Nasution, Riska; Yuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of social media among adolescents is increasing and has the potential to affect mental health. Junior high school students are a group that is vulnerable to emotional, behavioral, and social relationship disorders due to high digital exposure. The main problems in this study are the high intensity of social media use among students at SMP Negeri 6 Kota Jambi and the high proportion of abnormal mental health. This study aims to determine the relationship between social media use and mental health among adolescents at SMP Negeri 6 Kota Jambi. This study uses acorrelative descriptive design with a cross-sectional approach. The study population consists of all students in grades VII–IX, and the sample consists of 101 respondents selected using stratified random sampling. The independent variable was social media use, and the dependent variable was mental health, which was measured using the Strengths and Difficulties Questionnaire (SDQ). Data collection was conducted through the distribution of questionnaires, which were then analyzed using the Kendall Tau test. The results showed that most adolescents were in the frequent social media use category (53.5%), and most had abnormal mental health (86.1%). Bivariate analysis showed a significant relationship between social media use and mental health (p = 0.001) with a correlation strength of r = 0.321, which means a moderate positive relationship. The conclusion of this study is that the higher the social media use, the worse the mental health condition of adolescents.